The Value of Maqashid Syariah and Institutional Reputation in Decisions on the Use of Marhamah Savings: Nilai Maqashid Syariah dan Reputasi Lembaga dalam Keputusan Penggunaan Tabungan Marhamah - Miftahul Jannah; Ahmad Perdana Indra; Tuti Anggraini (Academia Open, 2025)
General Background: The growth of Islamic banking in Indonesia continues to show promise, yet market penetration remains limited due to competition with conventional banking. Specific Background: Customer decisions are influenced by both the application of Maqashid Syariah values and institutional reputation, yet limited studies assess both variables in the context of specific products like Marhamah Savings. Knowledge Gap: Previous studies overlook the combined impact of Maqashid Syariah values and institutional reputation on product usage decisions in localized banking contexts. Aims: This study investigates the influence of Maqashid Syariah values and institutional reputation on customers’ decisions to use Marhamah Savings at Bank Sumut Syariah, Medan. Results: Using a quantitative approach and regression analysis on 100 respondents, results indicate that both Maqashid Syariah values (t = 4.875; p < 0.001) and institutional reputation (t = 4.530; p < 0.001) significantly influence product usage decisions, jointly explaining 68.3% of the variance. Novelty: This study uniquely combines two critical factors—Shariah values and reputation—on a specific Islamic savings product in a regional context, offering fresh empirical insight. Implications: Findings suggest that Islamic banks should enhance service transparency, digital innovation, and public literacy based on Maqashid Syariah to improve competitiveness and customer loyalty.Highlight : Maqashid Syariah values positively influence the decision to use Marhamah Savings. Institutional reputation strengthens customer trust in Islamic banking products. Both factors together contribute significantly (68.3%) to usage decisions. Keywords : Maqashid Syariah, Institutional Reputation, Usage Decision, Marhamah Savings, Islamic Banking